Exploring the impact of urbanization on urban building carbon emissions in China: Evidence from a provincial panel data model. (May 2020) - Huo, Tengfei; Li, Xiaohui; Cai, Weiguang; Zuo, Jian; Jia, Fuyuan; Wei, Haifeng
Highlights: Estimates China's provincial urban building carbon emissions from 2000 to 2015 with China Energy Statistical Yearbook—Energy Balance Sheet- based splitting method (CESY-EBSM) . Establishes a comprehensive framework to systematically explore the multiple effects exerted by urbanization on urban building carbon emissions. Uses panel data model to explore urbanization effects from quantitative and structural dimensions. The evaluation indicators are from three perspectives: population, economy and space. Considers the impact of climate factors on urban building carbon emissions. Abstract: Urbanization is a significant factor for soaring building carbon emissions. However, few studies have explored how the urbanization influences urban building carbon emissions. This study attempts to establish a comprehensive framework for urbanization and systematically explore the multiple effects exerted by urbanization on urban building carbon emissions from both quantity and structure dimensions based on the STIRPAT model, using the panel data of China's 30 provinces from 2000 to 2015. Urbanization is measured from three perspectives: population, economy and space. Results show that the urban population and urban building floor space contribute negatively to the carbon emissions in the urban building sector, while the added value of the tertiary industry positively influences urban building carbon emissions in the quantity dimension. In the structure dimension, the percentage of the urban population on the total population exerts a positive impact on the increase of urban building carbon emissions, but the percentage of the tertiary industry and the plot ratio of the urban buildings play a role in cutting down urban building carbon emissions. This study provides deeper insights for the concomitant effects of urbanization on carbon emissions and can be conducive to the realization of energy conservation and carbon emission targets.